Evaluation practices in the light of the competency approach: Achievement Evaluation as a model - Mouras, Mahbouba; Aimeur, Sihem (Journal of Human Sciences, 2022)
The present study aims to reveal the field evaluation practices carried out by mathematics teachers in the intermediate education stage, to evaluate the work and achievements of students in the framework of the implementation of the reforms of the Algerian educational system since 2003. These reforms brought a qualitative jump in the field of educational evaluation beyond traditional concepts and practices to wider horizons with new self-imposed concepts and practices, based on the description of their field performance through the answers they provided during their interviews.